Streptococcus mutans membrane vesicles inhibit the biofilm formation of Streptococcus gordonii and Streptococcus sanguinis - Guxin Cui; Pengpeng Li; Ruixue Wu; Huancai Lin (AMB Express, 2022)
Abstract Streptococcus mutans, whose main virulence factor is glucosyltransferase (Gtf), has a substantial impact on the development of dental caries. S. mutans membrane vesicles (MVs), which are rich in Gtfs, have been shown to affect biofilm formation of other microorganisms. Streptococcus gordonii and Streptococcus sanguinis are initial colonizers of tooth surfaces, which provide attachment sites for subsequent microorganisms and are crucial in the development of oral biofilms. S. mutans and S. gordonii, as well as S. mutans and S. sanguinis, have a complex competitive and cooperative relationship, but it is unclear whether S. mutans MVs play a role in these interspecific interactions. Therefore, we co-cultured S. mutans MVs, having or lacking Gtfs, with S. gordonii and S. sanguinis. Our results showed that S. mutans MVs inhibited biofilm formation of S. gordonii and S. sanguinis but did not affect their planktonic growth; contrastingly, S. mutans ΔgtfBC mutant MVs had little effect on both their growth and biofilm formation. Additionally, there were fewer and more dispersed bacteria in the biofilms of the S. mutans MV-treated group than that in the control group. Furthermore, the expression levels of the biofilm-related virulence factors GtfG, GtfP, and SpxB in S. gordonii and S. sanguinis were significantly downregulated in response to S. mutans MVs. In conclusion, the results of our study showed that S. mutans MVs inhibited biofilm formation of S. gordonii and S. sanguinis, revealing an important role for MVs in interspecific interactions.